1984
DOI: 10.1258/002367784780958303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of faecal flora of cats based on different housing conditions with special reference to Bifidobacterium

Abstract: Faecal flora of cats was compared in different colonies. In conventional cats there were no significant qualitative differences in composition of faecal flora in 3 colonies but there was variation in numbers of enterobacteriaceae, streptococci, bifidobacteria and clostridia, Bacteroidaceae and eubacteria were the most predominant nora followed by clostridia, streptococci and lactobacilli. In SPF cats produced by hysterectomy, the numbers of clostridia and enterobacteriaceae and the frequency of occurrence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Previous studies are consistent with our findings where Bacteroides spp. have been reported to be a common bacterial group in the feline large intestine (Osbaldiston & Stowe, 1971; Itoh et al , 1984). However, in contrast, Bacteroidetes and Fusobacteria have been routinely cultured from duodenal aspirates using culture‐based methods (Papasouliotis et al , 1998; Johnston et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies are consistent with our findings where Bacteroides spp. have been reported to be a common bacterial group in the feline large intestine (Osbaldiston & Stowe, 1971; Itoh et al , 1984). However, in contrast, Bacteroidetes and Fusobacteria have been routinely cultured from duodenal aspirates using culture‐based methods (Papasouliotis et al , 1998; Johnston et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Bifidobacterium spp. were cultured from feces in 60% of healthy cats (Itoh et al , 1984). Also, another study utilizing FISH analysis of fecal extracts reported the detection of Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations